A statistical exploration of data to identify the role of cultivar and origin in the concentration and composition of yeast assimilable nitrogen. (15th March 2019) - Petrovic, Gabriella; Kidd, Martin; Buica, Astrid
Highlights: This survey included 805 grape juice samples over 2 vintages in South Africa. Pinotage had the highest average YAN and Cabernet Franc the lowest. Cultivar was found to play a bigger role than origin in determining the level of YAN. More variance was found for the YAN level of white varieties than for red. Study demonstrates how to extract additional value from an unsupervised survey data. Abstract: The study was undertaken to gain insight into the nitrogen status of grape juices currently used to make commercial wines in South Africa. This was done as yeast assimilable nitrogen (YAN) is most often suspected as the cause for problematic fermentations and has major implications for the organoleptic qualities of the final product. Using exploratory statistical methods, this study explored the possibility of identifying the role of cultivar and grape-growing district in the determination of the concentration and composition of YAN. However, as the dataset was found to be non-parametric and heteroscedastic, paired with unequal sample sizes, data analysis was approached with caution. Through the use of various suitable statistical analyses, cultivar was shown to play the more important role in determining the concentration and composition of YAN.